Integration of Information Technology in The Strategic Management Process a Case at PT. Bangka TIN Industries - Febriana, Widia; Cahyadi, Irwan; Hayati, Ridha Nurul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to examine the role of information technology (IT) integration in strengthening strategic management practices at PT. Bangka Tin Industri, a company engaged in mining and tin processing industry. As the sector faces increasing operational complexity and market uncertainty, the effective use of digital technologies becomes essential for sustaining competitiveness. This research adopts a qualitative case study approach to gain in-depth understanding of how IT supports strategic processes within the organization. Data were collected through semi-structured interviews with key managerial personnel, direct field observations, and a review of internal documents related to strategic planning and operational control. The findings reveal that the implementation of integrated information systems, particularly Enterprise Resource Planning (ERP) and Business Intelligence (BI), has contributed significantly to improving strategic formulation and execution. These systems enable real-time data access, enhance interdepartmental coordination, and provide analytical insights that support more informed and responsive decision-making. As a result, the company demonstrates greater strategic adaptability in responding to operational challenges and market dynamics. Despite these benefits, the study also identifies several obstacles that hinder optimal IT utilization. Organizational resistance to change, limited digital literacy among managerial staff, and the need for cultural adjustment emerge as key challenges during the digital transformation process. The results underscore the critical role of top management commitment, effective change management, and continuous capacity-building initiatives in ensuring successful IT integration. This study offers practical insights for mining and manufacturing firms seeking to align information technology with strategic management to navigate an increasingly dynamic business environment.